(untitled) (Intent Research Scientific Journal, 2023)
In political science, "Elite" is used in a morally neutral sense. When described in the most general forms, this concept refers to a group or layer whose political-administrative qualities and functions are clearly expressed. The theory of the elite strives to balance and exclude mediocrity in the evaluation of the influence of people on power and reflects the unequal, competitive, hierarchical, and growing character of the distribution of the influence of different people on power in the sphere of the political life of society. The scientific interpretation of the concept of "political elite" is based on certain general ideas about the place and role of politics, and its directly expressed signs in society. The theory of the political elite interprets it based on giving priority to management in the social structure of the economy and society, or its equal rights and uniformity.